2003
DOI: 10.1063/1.1584655
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependence of surface plasmon resonance of a Ti–SiO2 nanoparticle composite

Abstract: The linear optical absorption properties of a titanium nanoparticle composite formed by implantation of low energy Ti ϩ into single crystal SiO 2 are reported. Evolution of a surface plasmon resonance ͑SPR͒ induced by the formation of a metal nanoparticle composite is studied as a function of ion dose. At an implantation temperature of 25°C, the threshold dose for the appearance of the SPR is ϳ3.5ϫ10 16 ions/cm 2 , indicating that spontaneous nucleation and clustering of titanium nanoparticles in SiO 2 occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
4
9
0
Order By: Relevance
“…These high fluxes are also responsible for the very sharp size distribution of the embedded layer of NPs, as it has been previously observed that the size dispersion of NPs produced by ion implantation is substantially reduced when increasing the flux. 2,3 Our results give thus further support to the conclusion that low energy and high flux ion implantation is required to achieve narrow NP size distributions, 24,26 and provides an explanation for the narrow 2D distribution of Au NPs produced by ion implantation recently reported. 1 Although the kinetic energy ͑240 keV͒ in this report was higher than that used in the earlier ones, 2,3 the flux was close to 10 17 ions cm −2 s −1 and thus similar to the one used in this current work.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These high fluxes are also responsible for the very sharp size distribution of the embedded layer of NPs, as it has been previously observed that the size dispersion of NPs produced by ion implantation is substantially reduced when increasing the flux. 2,3 Our results give thus further support to the conclusion that low energy and high flux ion implantation is required to achieve narrow NP size distributions, 24,26 and provides an explanation for the narrow 2D distribution of Au NPs produced by ion implantation recently reported. 1 Although the kinetic energy ͑240 keV͒ in this report was higher than that used in the earlier ones, 2,3 the flux was close to 10 17 ions cm −2 s −1 and thus similar to the one used in this current work.…”
Section: Discussionsupporting
confidence: 73%
“…2,3 It has recently been shown that for Ti implantation at 9 keV and a total dose of 6 ϫ 10 16 ions cm −2 , a decrease of the flux by a factor of two causes the metal to form a quasi-continuous layer rather than NPs. 24 PLD is a transient process since most of the deposition occurs during a period of several microseconds after the laser pulse, with this deposition being repeated after a pause of some hundred milliseconds at a typical laser pulse frequency of 10 Hz. Considering 10 s as a conservative approximation for the deposition time after each pulse, the average flux per pulse of metal species arriving at the substrate using the rates plotted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On account of vigorous development of nanotechnology, the nanosized particles of various types are becoming the objects of intensive investigations [1][2][3][4]. The aqueous dispersions of SiO 2 nanoparticles belong to the most widely distributed colloidal systems [1,2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse reflectance spectra of TiO 2 anatase nanotubes were studied by Mor et al, who assigned an absorption peak near 450 nm to mid-gap defect states and/or plasmonic effects originated by unoxidized Ti; 63 this conclusion was based on the observed plasmonic behavior of Ti embedded in SiO 2 . 64 Defects within the bandgap of TiO 2 create a photoluminescence emission centered at around 2-2.5 eV, which was assigned to the recombination of excitons. 65,66 Despite being the first material to demonstrate water splitting under sunlight, the wide bandgap of TiO 2 is ill suited for solar cell or photoelectrochemical applications.…”
Section: Optoelectronic and Electrical Properties Of Tio 2 Nanotubesmentioning
confidence: 99%